The Urgency of Teacher Adaptation to Post-Online Face-to-Face Learning - Nurazila Sari; Na’imah Na’imah; Suyadi Suyadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The adaptation of teachers to face-to-face learning after online has become an urgent matter. Research shows the urgency of teacher adaptation to face-to-face learning after online, as happened at TK-IT Ibu Harapan Bengkalis. The research method used is a descriptive qualitative approach, with sources of document data and credible sources. Data was collected through observation, documentation, and in-depth interviews, and analyzed inductively. The results of the study show that Teachers who are able to adapt in teaching and learning activities will have a positive impact on students. The post-online learning system set by the government with a shift/sharing system is favored by teachers because it makes the process easier and achieves learning outcomes. The ability possessed by the teacher is growing for the better. So that teachers who are able to adjust or adapt become one of the components to create a better and more effective teaching and learning process.